**r**= ± 3 - √3, ± 1 - √3 so**r**IS i**r****r**ational the**r**efo**r**e it must be i**r****r**ational s = ±√[**r**^2 + (√3)**r**.... Solve the**r**esulting qua**r**tic equation:**r**^4 - 4**r**^2s^2 - 6**r**^2 + 4s^4 - 12s^2 + 9 = 0 fo**r**eithe**r**"**r**" o**r**...1 Answe

**r**s · Science & Mathematics · 24/01/2010Let

**r**= (x(1), x(2), ..., x(n)). So, |**r**...x(2))^2 + ... + (x(n))^2]. Hence,**r**(hat) = (x(1)/√[(x(1))^2 + (x(2))^2...x(1))^2 + ... + (x(n))^2)^(-1/2) = (n-1)/|**r**|. In the case whe**r**e n = 3, this ...1 Answe

**r**s · Science & Mathematics · 13/03/2013The correlation coefficient,

**r**, is a measure of the linear relationship between two variables. If...the data tends to have a negative slope. Positive values for**r**indicate the data tends to have a positive slope. if**r**= 0 we say the ...7 Answe

**r**s · Science & Mathematics · 03/01/2008**r**/5 + 6/5 =**r**/7 + 8/7 7r + 42 = 5r + 40 2r = - 2**r**= - 1 Answer:**r**= - 1 Checking: - 1/5 + 6/5 = - 1/7 + 8/7 5/5 = 7/7 1 = 12 Answe

**r**s · Science & Mathematics · 17/11/2010(

**r**− 3)(**r**+ 9)=-9 =>**r**(**r**+ 9) −3(**r**+ 9)= -9 =>**r**^2 + 9**r**−3**r**− 27 = -9 =>**r**^2 + 6**r**− 18 = 0 now...4 Answe

**r**s · Science & Mathematics · 15/12/2013(

**r**^2 - 4r - 5)/[5(**r**-5)] = (**r**-5)(**r**+1)/5(**r**-5) simplify by**r**-5: (**r**+1)/5 that's your result :) if you're not sure how to find roots of**r**^2 - 4r - 5, here's how you do it. 1. Find the delta (...5 Answe

**r**s · Science & Mathematics · 07/10/2011y =

**r***sin(T) We know that**r**= 5*sin(T) which gives sin(T) =**r**/5 And**r**^2 = x^2...3 Answe

**r**s · Science & Mathematics · 03/05/2010this can be written as

**r**^2 + 3r - 2 = 0 Now to solve this you can use the discriminat method (delta = b^2...the method of completing the square.**r**^2 + 3r + (3/2)^2 - (3.2)^2 -2 =0 (**r**+ 3/2)^2 = 9/4 + 2 = 17/4**r**+3/2 = +or- sqrt(17/4)**r**= + sqrt(17/4) - 3/2 or...3 Answe

**r**s · Science & Mathematics · 15/09/2010**R**= 1.1926, -4.1926 Try using MathWay.com Hope this helps!4 Answe

**r**s · Science & Mathematics · 07/04/2013✰Answe

**r**✰**r**= (-3y - 2k)/(a - 1) ✐De**r**ivation✐ 2k + a**r**=**r**- 3y T**r**y diffe**r**ent... is the bette**r**way to solve fo**r****r**. a**r**=**r**- 3y - 2k a**r**-**r**= -3y - 2k Facto**r**the left side.**r**(a - 1) = -3y - 2k**r**= (-3y - 2k)/(a...3 Answe

**r**s · Science & Mathematics · 27/07/2012